A Value chain analysis of B2B2C cross-border e-commerce for Chiang Mai fruit community enterprise - Yin Yilan (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
In recent years, Thailand exports fresh tropical fruits to China far exceeding other countries by type and amount, accounting for 24.68% of the total Chinese tropical fruits import. The Chinese market has expanded rapidly since the introduction of the Free Trade Agreement (FTA) between Thailand and China in 2003, after that Thai fruit exports to China has grown significantly. In 2009, Thailand fresh fruit export to China was worth 14.36 billion Baht, which soared up to 1.15 billion US dollars in 2016. Such growth rate has attracted many entrepreneurs in this business. The research has found that, there are three main types of business model for exporting Thai fruit to Chinese market. The first is the traditional B2B logistic model, and the second is the modern B2C e-commerce model, and the latest innovation B2B2C business model. The research applied a value chain analysis and supply chain analysis to evaluate these three models by analyzing the value and non-value activities of them. The result showed that, with a convenient cross-border transportation via R3A road and the rapid development of Chinese online platform, Chiang Mai fruit community enterprise could have easy access to connecting with customers directly and shipping to customers with competitive price. Therefore, this paper intends to create a knowledge map to share critical knowledge about how to develop innovation B2B2C business model to Chiang Mai fruit community enterprise. This new model not only increases the information flow efficiency by using online shopping platform, but also reduces the logistic cost by using multi-model transportation method (including: R3A road for cross border transportation and China domestic express delivery) to deliver the products to the end customers. The shortening of the supply chain also greatly guarantees the quality of the fruit, and the needs of customers can be better grasped, at the same time, the interests of the organization are guaranteed to the maximum extent.